Vulnerabilidade de sementes de Cenostigma pyramidale (TUL.) aos estresses abióticos - Matias, Janete Rodrigues (2019)
External factors may slow down, inhibit or promote germination. Understanding the mechanisms used in this process is extremely relevant because it allows, for example, the use of the species in future situations of greater intensity of environmental stresses. Insufficient plant tolerance to adverse environmental factors may threaten species viability. Surviving under stress depends on the ability of plant species to perceive the stimulus, generate and transmit the signal, presenting physiological, biochemical and enzymatic changes. In chapter 1, the objective was to evaluate the germination, vigor and metabolism of two accessions of Cenostigma pyramidale under conditions of salinity and water restriction at different temperatures. To simulate the stresses, solutions of sodium chloride and polyethylene glycol with osmotic potentials of -0,1; - 0.2, -0.4; -0.6 MPa e -0.1; -0.2; -0.3; -0.4, respectively, were used. For each treatment, 100 seeds, divided into four replicates, were used. The germination speed index, number of normal seedlings, length and dry mass of roots and aerial parts were evaluated. In addition, the content of total proteins, free amino acids and total soluble sugars were determined. The temperature influences the tolerance of C. pyramidale seeds to water restriction and salinity. The total soluble sugars, total proteins and amino acids present in seedlings of C. pyramidale respond as indicators of tolerance of this species to abiotic stresses. The accessions of C. pyramidale under abiotic stresses respond differently regarding germination, vigor and metabolism, with Bahia presenting a higher tolerance to salinity than that of Rio Grande do Norte. In the second chapter, the objective was to evaluate the germination and activity of antioxidant enzymes in two accesses of C. pyramidale under water restriction and salinity, at different temperatures. The accesses came from Bahia and Rio Grande do Norte. The germination was conducted under temperatures of 25, 30 and 35 ° C for 14 days, considering as germinated those ones with root protrusion. For the activity of the antioxidant enzymes, catalase, peroxidase and superoxide dismutase, under temperatures of 30 and 35 ° C, salinity and water restriction were simulated for the osmotic potencies of -0.1 and -0.4 MPa and of -0, 1 and -0.3 MPa, respectively. For this, the embryonic axes with 2 and 4 mm and their respective cotyledons were collected. The accessions of C. pyramidale differ in the enzymatic mechanism adopted in the signaling to the biotic stresses. The temperature influences the tolerance of C. pyramidale seeds to salinity and water restriction. The activities of the antioxidative enzymes in embryonic axes and cotyledons of C. pyramidale seedlings vary between accesses, temperatures and stresses. The evaluation of different accesses allowed a broad understanding regarding germination and biochemical and enzymatic mechanisms during the germination process under abiotic stresses